LEGO DC Universe super heroes : handbook. (Bradway, N.Y. : Scholastic, Inc., 2013)
This collection of facts about comic book super heroes and villains is illustrated with the Lego characters and structures associated with them.
Heroes! -- Villains! -- Vehicles! -- Locations!
K-3
NC1140L
4.6
Keywords: LEGO toys -- Juvenile literature; Superheroes -- Juvenile literature; Comic strip characters -- Juvenile literature; LEGO toys; Superheroes; Supervillains; Comic strip characters